2005
DOI: 10.1111/j.1600-0404.2004.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological features of motor neuron disease in south-western Greece

Abstract: There was no statistically significant difference in the results of the considered epidemiological parameters of our study to those reported by other similar studies. The study of the patients with MND showed a predominance of ALS patients. No potentially causative clinical associations were found and no relation between socioeconomic factors, occupational exposure and the disease was noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
6
24
1
9
Order By: Relevance
“…Alternatively, it may reflect improved detection methods, increased reporting rates, better access to medical care (with increased diagnostic rates) and refinement of epidemiological methods to study ALS 17 . Our findings suggest that, similarly to what has been reported by others, ALS is rare in the Brazilian population, although being the most prevalent of the motor neuron disorders 13,14 . Regarding patient-related characteristics, we found no differences in mortality by gender.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Alternatively, it may reflect improved detection methods, increased reporting rates, better access to medical care (with increased diagnostic rates) and refinement of epidemiological methods to study ALS 17 . Our findings suggest that, similarly to what has been reported by others, ALS is rare in the Brazilian population, although being the most prevalent of the motor neuron disorders 13,14 . Regarding patient-related characteristics, we found no differences in mortality by gender.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have investigated the prevalence of ALS, and better characterized samples have come from the in Europe and United States 13,14 . In Brazil few studies focused on the incidence of ALS, as well as on mortality rates associated with the disease, making it difficult to establish the magnitude and risk factors of ALS in our Country, justifying this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the present study found 127 men (55%) and 104 women (45%) with ALS. This predominance of males agrees with the studies by Lee et al 6 , McCombe and Henderson 3 , Zoccolella et al 15 , Argyriou et al 1 , Palermo et al 2 and Logroscino et al 4,5,16 . Some studies reported that this male preponderance is due to heavy industries and agricultural jobs 1,3,6,7 .…”
Section: Epidemiological Characteristicssupporting
confidence: 82%
“…Наводе се: тежак физички рад (45,48), интензивно бављење спортом (професионални фудбалери и маратонци), пушење, траума, излагање тешким металима, олову и живи (49,50,51). Регистрована је повећана учесталост механичке трауме у болесника са ALS у поређењу са контролном групом (32,52,53,54). Описан је двоструко већи број оболелих међу ветеранима Заливског рата 1991. г.…”
Section: идиопатски (примарни) Als и обухвата: -спорадичну Als (Sals)unclassified
“…Фамилијарна ALS (FALS) која је регистрована код 6.5% наших болесника је у распону учесталости који су регистровали и други аутори у различитим градовима света од 1.5% до 7% (54,151,215,286,340).…”
Section: фамилијарна амиотрофична латерална склерозаunclassified